Efforts to Prevent Violence and Sexual Abuse in Children (Case Study: SD Baitu Ilmin Surabaya) - Grace Dea Cahya Ayu Mumpuni; Dian Ety Mayasari (JURNAL HUKUM SEHASEN, 2023)
Sexual violence in Indonesia still occurs, especially sexual violence against children. In fact, in this case children also have the same rights as adults which are protected by the constitution. This happens because the provision of sexual education to children is still very taboo in Indonesia, therefore children's knowledge of sexuality and the things that lead to sexual violence have not been understood properly and clearly. Even though in this case, there are already legal arrangements related to sexual violence, in fact it is still not enough if it is not with the fulfillment of sexual education for children given by parents and teachers in schools. Therefore, it is not only the role of the government that is needed in preventing these crimes from occurring, but the community and families must also play a role in preventing these crimes. Therefore, in this study, it is hoped that parents and other communities will know that they must also play an active role in preventing sexual violence against children by providing proper and proper sexual education to children. Giving sexual education to children properly and appropriately turns out to also have a positive impact on children, not a negative impact as is thought by most people who think it is vulgar. Children who have been given sexual education will understand about the parts of the body that other people should not touch, the way they behave and the restrictions on the opposite sex, and how to refuse invitations from other people who have the intention of sexually assaulting them.